Pediatric Emergency Medicine Simulation Curriculum: Hyponatremic Seizures - Wee Chua; Rebekah Burns; Kimberly Stone; Jennifer Reid (Association of American Medical Colleges, 2016)
Abstract Introduction Seizures are a common complaint in the pediatric emergency department. Effective care of this potentially life-threatening medical emergency requires the ability to stabilize the patient while simultaneously identifying and treating the underlying cause. This simulation-based curriculum involves the identification and management of a generalized seizure in a 4-month-old infant secondary to hyponatremia. The target audience is pediatric and emergency medicine residents, fellows, faculty, and nurses. Methods There is no prerequisite preparation for the trainees prior to the case. The simulation scenario, simulation environment preparation, teamwork and communication glossary, and PowerPoint presentation are provided for the instructor in preparation for the simulation case. The setting is the emergency department (ED) resuscitation room. The simulation can be conducted in the ED resuscitation room or in the simulation lab. We used a high-fidelity infant mannequin. The debriefing tools have been tailored specifically for this scenario with advice on how the instructor can edit them for different learners. Results We have used this curriculum with a group of six pediatric emergency medicine fellows at various stages of their training at our institution. The curriculum received overwhelmingly positive feedback through the evaluation form. Discussion This resource will help support standardization of the teaching process, assisting simulation instructors to maximize their impact. In our experience, we have found that instructors who teach intermittently can successfully foster simulation-based education using similar resources. The inclusion of a learner feedback form supports the instructor's ongoing growth while helping faculty to document their teaching efforts.